Basic first aid (McGraw-Hill Higher Education, 2005)
The Basic First Aid is the go-to reference for emergencies that no home will want to be without. Full of practical, clear, and easy-to-understand advice, this resource ensures that every household is prepared for any type of medical situation. Includes line drawings and instructions to help people through emergency situations, as well as a medical information chart that everyone should have on hand.